Review of Perioperative Music Medicine: Mechanisms of Pain and Stress Reduction Around Surgery - Ginsberg, J. P.; Raghunathan, Karthik; Bassi, Gabriel; Ulloa, Luis (Frontiers in Medicine, 2022)
Clinical-experimental considerations and an approach to understanding the autonomic basis of improved surgical outcomes using Perioperative Music Medicine (PMM) are reviewed. Combined surgical, psycho-physiological, and experimental perspectives on Music Medicine (MM) and its relationship to autonomic nervous system (ANS) function are discussed. Considerations are given to the inter-related perioperative effects of MM on ANS, pain, and underlying vagal and other neural circuits involved in emotional regulation and dysregulation. Many surgical procedures are associated with significant pain, which is routinely treated with post-operative opioid medications, which cause detrimental side effects and delay recovery. Surgical trauma shifts the sympathetic ANS to a sustained activation impairing physiological homeostasis and causing psychological stress, as well as metabolic and immune dysfunction that contribute to postoperative mortality and morbidity. In this article, we propose a plan to operationalize the study of mechanisms mediating the effects of MM in perioperative settings of orthopedic surgery. These studies will be critical for the implementation of PMM as a routine clinical practice and to determine the potential limitations of MM in specific cohorts of patients and how to improve the treatment.